Peran Pendidikan Kewarganegaraan dalam Mengatasi Krisis Moral pada Pelajar di Era Globalisasi - Sri Yunita; Agnes Elizabeth Manalu; Fatma Angraini Lubis; Nabila Fri Cahyani; Ulan Ulan (Departement of Mathematics Education, 2024)
Morals are teachings that contain positive values ​​that are used as guidelines for wisdom and behavior based on a particular view of life or religious teachings. The purpose and function of morals is to regulate human behavior so that they consciously act in accordance with moral values. A student is someone who is an actor in education or a person who is educated and educated, in meaning and behavior a student must apply moral values, where these moral values ​​are courtesy, honesty, tolerance, kindness, kindness and justice. A student must uphold moral values. However, in the current era of globalization, students' moral values ​​are starting to decrease in terms of boundaries and actions. Citizenship education is a field of study that teaches moral and ethical values ​​in meaning and behavior for students. For this reason, in this case citizenship education plays a very important role in overcoming the moral crisis among students through teaching methods. Citizenship education can provide students with an understanding of moral values ​​and apply them in life at school and in society. This article will discuss the role of citizenship education in overcoming the moral crisis among students in the era of globalization. The aim of this research is to find out the steps taken through citizenship education in overcoming the moral crisis, especially for students.